Wav-audio steganography algorithm based on amplitude modifying - 邹明光; 李芝棠 (Tongxin xuebao)
Algorithms in different effective domains are analysed,and a wav-audio steganography algorithm based on amplitude modifying is proposed.The secret audio is scrambled through a random number generator.Amplitude values of each sampling point group are compared in original audio.While amplitude values are modified,the secret information bits are embedded.Embedding strength can be adjusted according to the key.Simulation results demonstrate that hiding capacity of this algorithm is large and good invisibility can be achieved.The anti-steganalysis ability of this algorithm is good and blind extraction can be realized.